2020
DOI: 10.1080/03009734.2020.1737599
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone agonist ovulation trigger—beyond OHSS prevention

Abstract: In this review the advantages of the gonadotropin-releasing hormone agonist (GnRHa) trigger are discussed beyond those immediately associated with ovarian hyperstimulation syndrome (OHSS) prevention. The GnRHa trigger concept has sparked the development of novel protocols, enriching the assisted reproductive technology (ART) armamentarium for the benefit of present and future patients. Thus, GnRHa trigger already has a pivotal role, not only for the standard in vitro fertilisation (IVF) patient, but also for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…This case should alert us to antagonist regimens and appropriate Gn initiation doses [9] should be chosen as much as possible in patients with ovarian hyper-responsiveness; the indications and dosages for the use of aspirin and low molecular heparin in IVF-ET should be strictly controlled [10,11] ; luteinizing support in IVF-ET should be avoided in multiple species overdose [12,13] ; anticoagulants should be discontinued promptly after the occurrence of bleeding disorders; after the occurrence of luteal rupture, conservative treatment can be taken for a certain period of time when the patient vital signs are stable and the disease is self-limiting in some patients. [14]…”
Section: Discussionmentioning
confidence: 99%
“…This case should alert us to antagonist regimens and appropriate Gn initiation doses [9] should be chosen as much as possible in patients with ovarian hyper-responsiveness; the indications and dosages for the use of aspirin and low molecular heparin in IVF-ET should be strictly controlled [10,11] ; luteinizing support in IVF-ET should be avoided in multiple species overdose [12,13] ; anticoagulants should be discontinued promptly after the occurrence of bleeding disorders; after the occurrence of luteal rupture, conservative treatment can be taken for a certain period of time when the patient vital signs are stable and the disease is self-limiting in some patients. [14]…”
Section: Discussionmentioning
confidence: 99%
“…there was notable change among the two groups Clinical pregnancy rate per embryo transfer. While there was no statistically important change among the two groups regarding Mild and moderate OHSS (p> 0.05) In addition, the study by Castillo et al,13 as they concluded that GnRHa trigger plays an important role beyond OHSS prevention.In contrast with our results the study by Mutlu et al,14 reported that Fertilization rates, implantation rates, clinical pregnancy rate per embryo transfer and live birth rate per embryo transfer were also greatly increased in the dual trigger group as compared to the hCG trigger group. The utilize of dual trigger with a Gonadotrophin releasing hormone agonist and a standard dosage of human chorionic gonadotrophin could advance clinical pregnancy percent and live birth levels in reduced ovarian responders go through GnRH antagonist IVF/ICSI cycles.CONCLUSIONThe use of Gonadotrophin releasing hormone agonist with low dose human chorionic gonadotrophin co-triggers was significantly prevent the risk of severe form not mild and moderate OHSS in women with polycystic ovarian disease in comparison with gonadotrophin releasing hormone agonist alone with better outcome.Conflict of interest : none 7.…”
mentioning
confidence: 87%
“…For instance, poor-responder women 178 or those requiring luteal support 179 , 180 might benefit from the addition of LH and hCG, respectively, during the management of an assisted reproductive cycle 154 , 179 . On the other hand, gonadotropin-releasing hormone (GnRH) agonists are now the alternative option to hCG to prime ovulation and reduce the risk of ovarian hyperstimulation syndrome 181 , 182 , but there are no clinical data comparing the effects of LH and hCG in men.…”
Section: Recent Advancesmentioning
confidence: 99%